Horizontally Acquired Biosynthesis Genes Boost Coxiella burnetii's Physiology - Moses, Abraham S.; Millar, Jess A.; Bonazzi, Matteo; Beare, Paul A.; Raghavan, Rahul (Frontiers in Cellular and Infection Microbiology, 2017)
Coxiella burnetii, the etiologic agent of acute Q fever and chronic endocarditis, has a unique biphasic life cycle, which includes a metabolically active intracellular form that occupies a large lysosome-derived acidic vacuole. C. burnetii is the only bacterium known to thrive within such an hostile intracellular niche, and this ability is fundamental to its pathogenicity; however, very little is known about genes that facilitate Coxiella’s intracellular growth. Recent studies indicate that C. burnetii evolved from a tick-associated ancestor and that the metabolic capabilities of C. burnetii are different from that of Coxiella-like bacteria found in ticks. Horizontally acquired genes that allow C. burnetii to infect and grow within mammalian cells likely facilitated the host shift; however, because of its obligate intracellular replication, C. burnetii would have lost most genes that have been rendered redundant due to the availability of metabolites within the host cell. Based on these observations, we reasoned that horizontally derived biosynthetic genes that have been retained in the reduced genome of C. burnetii are ideal candidates to begin to uncover its intracellular metabolic requirements. Our analyses identified a large number of putative foreign-origin genes in C. burnetii, including tRNAGlu2 that is potentially required for heme biosynthesis, and genes involved in the production of lipopolysaccharide — a virulence factor, and of critical metabolites such as fatty acids and biotin. In comparison to wild-type C. burnetii, a strain that lacks tRNAGlu2 exhibited reduced growth, indicating its importance to Coxiella’s physiology. Additionally, by using chemical agents that block heme and biotin biosyntheses, we show that these pathways are promising targets for the development of new anti-Coxiella therapies.